SOSIALISASI PENANGGULANGAN PENYALAHGUNAAN NARKOBA UNTUK MEWUJUDKAN SINTANG SAKTI DI SMA NEGERI 4 SINTANG - Fusnika, Fusnika; Septrianda, Milka; Kristiwinanda, Karissa (JURNAL PEKAN : Jurnal Pendidikan Kewarganegaraan, 2024)
The aim of the socialization activity on the dangers of drugs at Sintang State High School (SMA) 4 Sintang Regency, West Kalimantan is so that participants can understand the impacts of drug use, both physical, psychological and socio-economic. Socialization activities use participatory methods, lectures and discussions. The socialization activity was carried out on December 12 2023 with the number of participants taking part in the socialization activity consisting of 534 students and 3 teachers located in the classrooms and fields of SMA Negeri 4 Sintang. For this reason, through this socialization activity on the dangers of drug abuse, it is able to increase the understanding of students at SMA Negeri 4 Sintang regarding the types of narcotics, the impact of drug abuse from physical, psychological, educational, social and economic aspects as well as prevention and control methods including drugs among children and child. teenager. For this reason, this socialization activity can protect the younger generation as the nation's next generation, especially students at SMA Negeri 4 Sintang, Sintang Regency, West Kalimantan, from the dangers of drug abuse.Keywords: Dangers of Drug Abuse, Socialization, SintangÂ